Dialektika Poligami dan Feminisme: Analisis Pendampingan Kelas Poligami oleh Coach Hafidin di Indonesia dan Pemikiran Musdah Mulia tentang Poligami Buka di Google Terjemahan - Alifia Zahratul Adha; Bhirawa Anoraga (MUWAZAH : jurnal kajian gender, 2024)
Polygamy continues to generate deep contention within Muslim societies, particularly due to conflicting interpretations regarding its implications for gender justice. While Islamic teachings permit polygamy under strict conditions, its practice often triggers public debate over whether it reinforces patriarchal dominance or violates women’s rights. This study aims to critically examine the contrasting perspectives on polygamy through the lens of two influential figures: Coach Hafidin, who advocates for polygamy through paid mentoring programs, and Musdah Mulia, a leading feminist Muslim scholar who opposes it. Utilizing a qualitative content analysis approach, this research draws on primary data from video documentation—especially the Narasi Newsroom’s broadcast—and complementary secondary materials including academic literature and social media discourse. The findings reveal a fundamental dialectic between a religious-cultural defense of polygamy and feminist critiques that highlight the institutionalization of gender inequality. Coach Hafidin’s arguments frame polygamy as a legitimate, even necessary, religious practice, while Musdah Mulia deconstructs it as a form of gendered injustice that undermines women’s autonomy and dignity. This article underscores the need for contextual and ethical reconsiderations of polygamy, advocating for interpretations of Islamic teachings that prioritize justice, equality, and human dignity in contemporary Muslim life.